What makes a metaphor an embodied metaphor? - Daniel Casasanto; Tom Gijssels (2015)
Abstract What does it mean for metaphors to be “embodied”? Here we describe an influential theory of embodied cognition according to which thoughts are implemented in perceptuo-motor simulations, in the brain’s modality-specific systems. This theory is invoked in nearly every paper on “embodied metaphor,” across linguistics, philosophy, psychology, and cognitive neuroscience. There appears to be overwhelming support for the conclusion that representations of metaphorical “source domains” are embodied in perceptuo-motor simulations. Here we show, however, that when the data are evaluated appropriately there is very little evidence that metaphors are embodied in this sense. The kind of data that offer compelling support for the embodiment of concrete, literal ideas like “grasping the ball” are nearly absent for abstract, metaphorical ideas like “grasping the explanation.” There is now abundant evidence that metaphors structure our thoughts, feelings, and choices in a variety of conceptual domains. But evidence for metaphorical mental representation is not necessarily evidence for embodiment. If any metaphorical source domains are embodied in modality-specific simulations, they may be the exception rather than the rule.